Improved latrine coverage may reduce porcine cysticercosis: a comparative cross-sectional study, Busia County, Kenya 2021 - Chege, Bernard; Ndambuki, Gideon; Owiny, Maurice; Kiyong’a, Alice; Fèvre, Eric M.; Cook, Elizabeth A. J. (Frontiers in Veterinary Science, 2023)
Smallholder pig farming is an important economic activity for poor, rural communities in developing countries. Porcine cysticercosis is a growing public health risk in countries where pig rearing is popular. A sanitation-based intervention to reduce the prevalence of open defecation was completed in Busia County, Kenya in 2016. We capitalized on this third party intervention to evaluate its impact on porcine cysticercosis prevalence. We conducted a comparative cross-sectional survey from August to September 2021. Household selection was done using multistage sampling. Household questionnaire data on pig production, transmission, risk factors and awareness of porcine cysticercosis were collected from 251 households. Lingual palpation was used to test for cysticerci in 370 pigs while serum was tested for circulating antigen using Ag-ELISA. We compared results of our survey to an effective baseline, a near equivalent cross sectional survey conducted in 2012 before the sanitary intervention. The difference in prevalence was measured using Chi-square tests. Multivariable logistic regression analysis was used to identify risk factors for lingual cysts in pigs. The prevalence of palpable lingual cysts was estimated to be 3.8% (95% CI 2.3%-6.3%) (14/370). This was 6% (95% CI 0.8%-13.9%; p-value 0.0178) lower than the prevalence reported in the pre-implementation period of 9.7% (95% Cl. 4.5%–17.6%). Circulating antigen was detected in 2 samples (0.54%, 95% CI: 0.2-1.9). Latrine coverage was 86% (95% CI: 81%-90%), which was 11% (95% CI: 4.8%-16.8%; p< 0.001) higher than the pre-implementation period coverage of 75% (95% CI: 71-79%). There was reduced prevalence of lingual cysts in pigs from households that had a latrine (OR = 0.14; 95% CI 0.05-0.43; p <0.001) and where pigs were confined or tethered (OR = 0.27; 95% CI 0.07-1.02; p=0.053). There was a reduction in the prevalence of porcine cysticercosis in Busia County over the study period from 2012-2021. This was not a trial design so we are unable to directly link the decline to a specific cause, but the data are consistent with previous research indicating that improved sanitation reduces porcine cysticercosis. Programmes for controlling porcine cysticercosis should include a focus on sanitation in addition to other integrated One Health approaches.